Treatment of MRSA-infected osteomyelitis using bacterial capturing, magnetically targeted composites with microwave-assisted bacterial killing - Yuqian Qiao (Nature Portfolio, 2020)
Deep tissue infections can be difficult to treat due to limited light penetration associated with phototherapies. Here, the authors report on a bacterial capture system for antibiotic delivery and microwave-assisted killing of MRSA in osteomyelitis and demonstrate application in vivo.